Study of temperature rise of small brushed DC motor under different load - N. Fatimah, Abdullah; Abbas A., Wahab; Mohd Azri Hizami, Rasid (EDP Sciences, 2018)
The heating of brush DC motor in the various applications usually involves the thermal damage to the motor like demagnetization of the magnet and also leads to short circuit. Due to this problem, the temperatures at the sensitive components are needed to be observed for a different number of loads. So, the motor will be delivered some torque when running thus generating the different value of losses. In this paper, a healthy brush DC motor is being used to observed temperature rise from the brush through the motors’ component and lastly to the outer space of the motor. Hence, discussion on the pattern of temperature rise will be discussed.